Social network analysis in the classroom: A case study - Vieytes, Jessica M. (AWARI, 2023)
The Social Network Analysis (SNA) based on graph theory is employed to diagnose the composition, position of actors, and community distribution within a social network. Understanding these factors is crucial in the educational context, as affective relationships have been shown to influence students' academic performance. This study focuses on a specific case to identify choice and rejection relationships among students, roles, and subgroup compositions, aiming to implement strategies to enhance the classroom climate. With a descriptive scope and cross-sectional experimental design, the research applies SNA methods and a sociometric questionnaire to a group of 33 sixth-grade high school students. Classic software tools were employed to organize, present, and analyze the data (Gephi and NodeXL). Findings indicate that the analyzed network lacks concentration in choice relationships, spreading through reciprocal links. However, rejection relationships tend to centralize among a few students, highlighting the vulnerability of a particular student facing high rejection despite occupying a privileged bridge position between gender communities. The group exhibits strong segmentation into communities with high internal cohesion but low interconnection, primarily composed of students of the same gender. This contributes to and reinforces the overall lack of integration within the studied group.